Management of inquiries into disasters : experts views and perspectives. - Mat Said, Aini (Weston Medical Publishing, LLC, 2008)
In most democratic countries, inquiries are conducted into major accidents. One of the main functions of inquiries into disasters is to establish the causes and to learn lessons from them so as to prevent a recurrence. However, previous studies showed that the learning aspect is often curtailed because of the inadequate guides to the conduct and procedures of inquiry management. A study was conducted to determine the disaster experts’ views and perspectives on management of disaster inquiries.